2019
DOI: 10.1021/acs.joc.9b02068
|View full text |Cite
|
Sign up to set email alerts
|

Direct Amidation of Carboxylic Acids with Nitroarenes

Abstract: N-Aryl amides are an important class of compounds in pharmaceutical and agrochemical chemistry. Rapid and low-cost synthesis of N-aryl amides remains in high demand. Herein, we disclose an operationally simple process to access N-aryl amides directly from readily available nitroarenes and carboxylic acids as coupling substrates. This method involves the in situ activation of carboxylic acids to acyloxyphosphonium salt for one-pot amidation, without the need for isolation of the corresponding synthetic intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 91 publications
0
48
0
Order By: Relevance
“…Ma and co-workers described the synthesis of amides 93 from nitroarenes 1 and carboxylic acids 92 by the use of Mn/ TMSCl in the presence of PPh 3 and I 2 (Scheme 33). [34] The protocol was viable for the synthesis of several drug like molecules and agrochemical compounds. This work was inspired from earlier reports wherein the synthesis of Weinreb amides was achieved via reaction between acids and amines in the presence of PPh 3 and I 2 by Lakshman et al [35] Analogous to this work, these workers too suggested the formation of acyl iodide 95 from acyloxyphosphonium iodide 94, which in turn was formed via reaction of acid with PPh 3 and I 2 .…”
Section: Amidation Of Acidsmentioning
confidence: 99%
“…Ma and co-workers described the synthesis of amides 93 from nitroarenes 1 and carboxylic acids 92 by the use of Mn/ TMSCl in the presence of PPh 3 and I 2 (Scheme 33). [34] The protocol was viable for the synthesis of several drug like molecules and agrochemical compounds. This work was inspired from earlier reports wherein the synthesis of Weinreb amides was achieved via reaction between acids and amines in the presence of PPh 3 and I 2 by Lakshman et al [35] Analogous to this work, these workers too suggested the formation of acyl iodide 95 from acyloxyphosphonium iodide 94, which in turn was formed via reaction of acid with PPh 3 and I 2 .…”
Section: Amidation Of Acidsmentioning
confidence: 99%
“…PPh 3 /I 2 system was complimentary to the activator. The Phakhodee group reported an example of amidation of cinnamic acid with tertiary amine.…”
Section: Acids As Nucleophiliesmentioning
confidence: 99%
“…Acyloxyphosphonium intermediate formed by the aid of iodiophosphonium ion. In 2019, the Ma group reported the direct amidation of cinnamic acids with nitroarenes. This method also involved the in situ activation of acids to acyloxyphosphonium salt.…”
Section: Acids As Nucleophiliesmentioning
confidence: 99%
“…1a ) 8 19 . Nitroarenes are readily available and cheap feedstock reagents 20 27 and have recently been applied with reduction in situ as amination reagents in amidation 28 – 30 . For example, Ma et al recently achieved an elegant one-pot stoichiometric amidation protocol of carboxylic acids with nitroarenes 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Nitroarenes are readily available and cheap feedstock reagents 20 27 and have recently been applied with reduction in situ as amination reagents in amidation 28 – 30 . For example, Ma et al recently achieved an elegant one-pot stoichiometric amidation protocol of carboxylic acids with nitroarenes 30 . Although these typical amide bond formation strategies are powerful, the development of a catalytic amidation protocol of carboxylic acids is still being actively pursued in the context of sustainable synthetic chemistry 1 , 31 as the carboxylic acid activating reagents not only result in some harmful byproducts but also would compromise the functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%